Intra-athlete and inter-group comparisons: Running pace and step characteristics of elite athletes in the 400-m hurdles - Otsuka, M.; Isaka, T. (PLOS ONE, 2018)
The aim of this study was to investigate the running pace and step characteristics among various competitive-level 400-m hurdlers through inter-group and intra-athlete comparisons. We analysed spatiotemporal data involving the split time, mean step length (SL) and mean step frequency (SF) for 13 male world-class and 14 male national-level 400-m hurdlers. We analysed 16.5 ± 3.9 races for each world-class hurdler and 19.8 ± 6.0 races for each national-level hurdler (the total number of analysed runs was 491) using publicly available television and internet broadcasts. Inter-group comparisons showed that both first- and latter-halves split times of the world-class hurdlers were significantly shorter than those of the national-level hurdlers. In the latter-half phase, no significant differences of SL and SF were observed between the world-class and national level hurdlers. Intra-athlete comparisons showed that no athletes favoured only first-half phase in terms of running speed in short finish times. In contrast, finish times of all hurdlers were sensitive to running speed in the latter-half phase. In the latter half of the race, 18 of the 27 hurdlers were identified as being SF reliant during speed enhancements; running speed of the other 9 hurdlers were also sensitive to high SF. In conclusions, important findings regarding high performance in inter-group comparisons do not always corresponded with those in intra-athlete comparisons. All athletes and coaches should first prioritize maintaining high running speeds in the latter half of 400-m hurdles rather than in the first half of the race.